2013
DOI: 10.1111/fwb.12143
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of the cyanobacterium Microcystis aeruginosa on the growth and physiology of two green algae, Oocystis marsonii and Scenedesmus obliquus, revealed by flow cytometry

Abstract: Summary Aquatic photosynthetic productivity is influenced by resource availability, resource use efficiency and interspecific interactions. In hypertrophic environments, interspecific interference is known to influence species succession. The effect of interference by phytoplankton on biomass production is very poorly understood. One hypothesis is that the development of cyanobacterial blooms is triggered by the excretion of allelopathic substances that inhibit the growth of other phytoplankton species. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 67 publications
(149 reference statements)
0
21
0
Order By: Relevance
“…Direct cultivation of strains/species allowing cell‐to‐cell interaction is a more realistic approach to mimic interspecific interaction. Recent studies have shown stronger growth inhibition in green algae and diatoms in direct co‐cultivation with M. aeruginosa than in membrane‐separated co‐culture or with cyanobacteria exudates (Dunker et al ., ; ; Wang et al ., ). However, direct co‐cultivation does not as easily allow for monitoring the respective physiological and metabolic responses of both interacting organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Direct cultivation of strains/species allowing cell‐to‐cell interaction is a more realistic approach to mimic interspecific interaction. Recent studies have shown stronger growth inhibition in green algae and diatoms in direct co‐cultivation with M. aeruginosa than in membrane‐separated co‐culture or with cyanobacteria exudates (Dunker et al ., ; ; Wang et al ., ). However, direct co‐cultivation does not as easily allow for monitoring the respective physiological and metabolic responses of both interacting organisms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that green algae Quadrigula chodatii grew significantly better than nontoxic M. aeruginosa PCC7820 under co-cultured conditions (Zhang et al, 2013b). Furthermore, green algae Scenedesmus obliquus was observed to benefit from the competition with toxic M. aeruginosa strains (Dunker et al, 2013;Harel et al, 2013). It has been suggested that allelopathy and competition to affect algal predominance during cyanobacteria bloom-forming, especially the dominance of Microcystis species (Chen et al, 2003;Yamamoto and Nakahara, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, unfavorable and sub-optimal conditions reducing photosynthetic efficiency and growth may arise from direct interactions between phytoplankters. For example, some green algae and cyanobacteria produce secondary metabolites that inhibit photosynthesis and growth of their competitors (e.g., Dunker et al 2013, Harel et al 2013, Zhang et al 2013. The detection of such allelopathic interactions was beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 96%
“…In general, a reduction of photosynthetic efficiency and growth can be interpreted as a reaction to sub-optimal, resource-limiting conditions (c.f. Morris 1976, Spijkerman 2010 thesis and growth of their competitors (e.g., Dunker et al 2013, Harel et al 2013, Zhang et al 2013. In response, species may adjust their biochemical composition.…”
Section: Introductionmentioning
confidence: 99%